2016
DOI: 10.1021/jacs.6b06778
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the pH-Dependent Selectivity of the Oxygen Reduction Reaction Electrocatalyzed by N-Doped Graphitic Carbon

Abstract: Nitrogen-doped graphitic carbon materials have been extensively studied as potential replacements for Pt-based electrocatalysts for the oxygen reduction reaction (ORR). However, little is known about the catalytic mechanisms, including the parameters that determine the selectivity of the reaction. By comparing theoretical calculations of the ORR selectivity at a well-defined graphene nanostructure with experimental results, we propose a model based on interfacial solvation to explain the observed preference fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 105 publications
6
89
1
Order By: Relevance
“…Moreover, among the pyridinic-N-doped nanographenes, the larger ones displayed higher activities in the ORR, probably due to the higher HOMO levels, which facilitated the electron transfer to oxygen. Further theoretical studies on compound 252 suggested that the ORR preferred the four-electron pathway in alkaline electrolytes but the two-electron pathway in acidic conditions, consistent with the experimental pH-dependent selectivity observed in the ORR catalyzed by N-doped graphene [312]. This work confirmed the electroactivity of the pyridinic-N atoms, providing clear insights into the more complex N-doped graphene; thus, synthesizing nanographene molecules with different types of nitrogens would be desirable.…”
Section: Heteroatom Dopingsupporting
confidence: 71%
“…Moreover, among the pyridinic-N-doped nanographenes, the larger ones displayed higher activities in the ORR, probably due to the higher HOMO levels, which facilitated the electron transfer to oxygen. Further theoretical studies on compound 252 suggested that the ORR preferred the four-electron pathway in alkaline electrolytes but the two-electron pathway in acidic conditions, consistent with the experimental pH-dependent selectivity observed in the ORR catalyzed by N-doped graphene [312]. This work confirmed the electroactivity of the pyridinic-N atoms, providing clear insights into the more complex N-doped graphene; thus, synthesizing nanographene molecules with different types of nitrogens would be desirable.…”
Section: Heteroatom Dopingsupporting
confidence: 71%
“…

controlled to obtain efficient activities; otherwise the porous structures might collapse, and the active centers might be hindered. [10][11][12][13][14] Such catalysts should be further explored to fulfill the requirements of cell optimizations and applications.Combining MOFs with carbon materials, such as graphene or carbon nanotubes to enhance performance has been widely studied in the fields of sensing, [15,16] separation, [17] catalysis, [18] supercapacitor, [19] etc. On the other hand, the mechanisms to provide high activities are convoluted due to the diversity of potential functional centers in such materials.

…”
mentioning
confidence: 99%
“…Based on the theoretical model for the pH‐dependent electrocatalytic activities of nitrogen incorporated graphenes, a similar mechanism is proposed to explain the observed ORR activity of N−Gr at different pH, as shown in Figure . The ORR and its mechanistic pathways can be affected by the pH, the interfacial solvation, the dielectric constants of the electrolyte (medium), the activation barrier, and the free energy change.…”
Section: Resultsmentioning
confidence: 99%
“…When the N−Gr is placed in an O 2 saturated electrolyte, it forms a peroxygraphene anion by the chemisorption of molecular oxygen. Breaking of either O−O or C−O bond in the peroxy graphene anion rules the mechanism of the ORR, i. e. the breaking of O−O leads to 4e − pathway and the breaking C−O leads to 2e − pathway . However, the breaking of these bonds depends on the factors mentioned above.…”
Section: Resultsmentioning
confidence: 99%